Pemodelan Instrumen Pengukuran Tingkat Penerimaan Penggunaan Sistem Informasi Studi kasus: Penerimaan Aplikasi Verifikasi Industri pada Sebuah BUMN - Al Anshary, Faishal Mufied (Jurnal Rekayasa Sistem & Industri, 2018)
PT ABC is in charge of verifying the industries. The verification process uses an information system that has been instructed by the Ministry of the Republic of Indonesia. But the low level of acceptance of information systems in PT ABC becomes an obstacle. This study aims to explore the causes of low levels of acceptance of information systems in PT ABC by using the acceptance model UTAUT. From UTAUT model, it can be identified factors that influence low acceptance level. The end result of this research is a recommendation for PT ABC regarding the improvement of industrial verification information system. This research propose four items: policy to users, formalizing business processes and increasing awareness about the importance of using information system to user level.